2013
DOI: 10.1007/978-3-642-39357-0_4
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Data Analysis of Harmonic Structures in Popular Music

Abstract: While analysing large corpora of music, many of the questions that arise involve the proportion of some musical entity relative to one or more similar entities, for example, the relative proportions of tonic, dominant, and subdominant chords. Traditional statistical techniques, however, are fraught with problems when answering such questions. Compositional data analysis is a more suitable approach, based on sounder mathematical (and musicological) ground. This paper introduces some basic techniques of composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 18 publications
4
30
0
Order By: Relevance
“…De Clercq and Temperley (2011, p. 50) produced what they called "one of the first, large-scale, systematic corpus analyses of popular music" with the aim of developing a foundation of stylistic norms in rock music upon which future research could be built. Under the auspices of the McGill Billboard Project, Burgoyne (2012) and Burgoyne, Wild, and Fujinaga (2013) explored the use of mathematical and computational methods to statistically analyze harmonic progressions. More recently, corpus studies have proliferated hip-hop scholarship: Ohriner (2016) has worked toward similar goals as de Clercq and Temperley, aiming to provide a representative sample of stylistic norms (in this case concerning hip-hop flow) against which outlying musical examples can be situated.…”
Section: Corpus Analysismentioning
confidence: 99%
“…De Clercq and Temperley (2011, p. 50) produced what they called "one of the first, large-scale, systematic corpus analyses of popular music" with the aim of developing a foundation of stylistic norms in rock music upon which future research could be built. Under the auspices of the McGill Billboard Project, Burgoyne (2012) and Burgoyne, Wild, and Fujinaga (2013) explored the use of mathematical and computational methods to statistically analyze harmonic progressions. More recently, corpus studies have proliferated hip-hop scholarship: Ohriner (2016) has worked toward similar goals as de Clercq and Temperley, aiming to provide a representative sample of stylistic norms (in this case concerning hip-hop flow) against which outlying musical examples can be situated.…”
Section: Corpus Analysismentioning
confidence: 99%
“…For example, the musical chords and voice leadings were modelled by geometric space [ 6 , 7 ]. The topology analysis [ 8 ] and compositional data analysis [ 9 ] were both used to investigate musical structures. Johannes Kepler’s “ The Harmony of the World ” was inspired by music [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the recurrence of characteristic motifs is the most important feature for establishing similarity in Dutch folk melodies. Musicological hypotheses were also tested in a study of harmonic usage in American popular music as it evolved from the 1950s to the 1990s(Burgoyne, Wild, & Fujinaga, 2013). The authors used 1379 songs from the Billboard dataset with chord transcriptions manually annotated by experts(Burgoyne, Wild, & Fujinaga, 2011), and performed compositional data analysis to illustrate changes in harmonic usage over time.…”
mentioning
confidence: 99%